PERUBAHAN UNDANG-UNDANG DASAR 1945: SEBUAH KENISCAYAAN - Darnela, Lindra (De Jure: Jurnal Hukum dan Syari'ah, 2010)
TheÂ  1945Â  ConstitutionÂ  ofÂ  IndonesianÂ  RepublicÂ  (UUDÂ  1945)Â  hasÂ  beenÂ  aÂ  setÂ  ofÂ  sacredÂ  norm and national administration reference for four decades. However, since the reform era Indonesian people are now able to review, discuss, and criticize its content consistent with recent national progress. Amendment of the 1945 Constitution becomes a new momentum to improve the stateâ€™s management, which has apparently deviated from the countryâ€™s foremost objectives written in the national philosophy of â€œPancasilaâ€. In response to the amendment, there are three diverse perspectives that highlight its process. First, there are people who wish to keep the ori ginality of the 1945 Constitution. Second, there are individuals who agree with the last amendment of the 1945 Constitution. Lastly, there is a public view which supports the continuous amendment process of the 1945 Constitution until it achieves the supreme mandate of the country and the people. This paper will focus on the third perspective as the main issue of discussion. UUD 1945 telah menjadi norma yang sakral dan referensi administrasi nasional selama empat dekade ini.Akan tetapi, sejak era reformasi masayarakat Indonesia mampu mereview, endiskusikan dan mengkritik isi dari UUD 1945 seiring dengan keajuan bangsa saat ini. Perubahan UUD 1945 menjadi momentum untuk meningkatkan manajemen Negara yang nampaknya menyimpang dari tujuan Negara pada awalnya yang tercantum dalam pancasila. Dalam menyikapi perubahan UUD 1945 tersebut, ada tiga pendapat yang berbeda yang menggarisbawahi proses tersebut. Yang pertama, sebagian masyarakat menginginkan keaslian dari UUD 1945. Yang kedua, sebagian masayarakat menginginkan perubahan terkhir dari UUD 1945. YangÂ  terakhir,Â  adaÂ  pendapatÂ  publikÂ  yangÂ  mendukungÂ  keberlanjutanÂ  dariÂ  prosesÂ  perubahan UUD 1945 hingga mencapai mandat tertinggi dari Negara dan rakyat. Tulisan ini secara fokus akan mendiskusikan isu dari pendapat yang terakhir dari amandemen UUD 1945